Canning of tropical mushroom (Valvariella Volvacea Singer) - Cunamay, Erlinda T.; Gatchalian, Miflora M. (1972)
ABSTRACT This study was undertaken to develop a procedure and standardized formulation for canning of straw mushrooms comparable if not better, than those imported from Taiwan. Brine concentration in packing medium was varied in order to arrive at the most acceptable one. Also, optimum processing time was determined by varying processing time and by heat penetration study. A standardized procedure and formula using 2% salt concentration and processing at 30 minutes at 10 psi pressure was arrived at from the results of the tests conducted which included cut-out, chemical, microbiological tests and subjective evaluation.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mushrooms